2020
DOI: 10.24320/redie.2020.22.e30.2750
|View full text |Cite
|
Sign up to set email alerts
|

Competencias del ingeniero industrial en la Industria 4.0

Abstract: El contexto actual de la Industria 4.0 está cambiando la formación de los ingenieros, de tal forma que las universidades implementan estrategias y acciones para adaptar los planes de estudio a los requisitos de la nueva revolución industrial. En este trabajo se realizó una investigación cualitativa de carácter bibliográfico y documental para identificar las principales competencias que debe desarrollar un ingeniero industrial, posteriormente se realizó un análisis curricular tomando como ejemplo a una universi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The bibliographic review corresponding to stage 1 of phase I showed from an international point of view that the current training itinerary of the ICI-UC Temuco degree provides training similar to the American one and addresses necessary and appropriate topics to practice the profession of industrial civil engineer in Chile, such as management and optimization. However, authors such as Sari and González-Hernández and Granillo-Macías suggest that, to face the world of work, the Industrial Civil Engineer must academically address: (i) inferential statistics, (ii) multivariate statistical methods, (iii) big data, (iv) data envelope analysis, (v) theory of solving inventive problems and (vi) programming and use of software relevant to the specialty [3,14]. This information is supported by a study published by The Organization of American States, which showed that the prioritized areas that can directly impact the development of Industrial Civil Engineering in the coming years are New Technologies (includes all technological advances in the industry).…”
Section: Main Results Of Phase Imentioning
confidence: 99%
See 1 more Smart Citation
“…The bibliographic review corresponding to stage 1 of phase I showed from an international point of view that the current training itinerary of the ICI-UC Temuco degree provides training similar to the American one and addresses necessary and appropriate topics to practice the profession of industrial civil engineer in Chile, such as management and optimization. However, authors such as Sari and González-Hernández and Granillo-Macías suggest that, to face the world of work, the Industrial Civil Engineer must academically address: (i) inferential statistics, (ii) multivariate statistical methods, (iii) big data, (iv) data envelope analysis, (v) theory of solving inventive problems and (vi) programming and use of software relevant to the specialty [3,14]. This information is supported by a study published by The Organization of American States, which showed that the prioritized areas that can directly impact the development of Industrial Civil Engineering in the coming years are New Technologies (includes all technological advances in the industry).…”
Section: Main Results Of Phase Imentioning
confidence: 99%
“…In recent decades, the complexity of society and its organizations in a global world has increased, which, together with the intensification of international competition, the growing volatility of the market and demand for personalized products, has forced the industry to adopt the use and application of cybernetic systems, cloud computing, internet of things, big data, analytics, among others [1][2]. This continuous challenge for the industry is reflected in industrial engineering, which has experienced various changes; evolving from rather mechanical methods to electronic or automated methods; from qualitative procedures to new techniques that require modeling, simulation, programming and extensive use of data analysis sciences and statistics; from an approach focused mainly on production and its efficiency to an integrative approach that considers the environment, the development of people, the company's strategy, value addition, among many other elements [3][4]. Interest is now focused on macrosystems, and on the design, management and analysis of larger, more complex systems [5].…”
Section: Introductionmentioning
confidence: 99%
“…Complexes of an integrated system consisting in people, money, knowledge, information, equipment, energy, and materials. Since the beginning of industrialization, technological leaps have given rise to paradigmatic changes called "industrial revolutions": first, in the field of mechanization; second, in the intensive use of electrical energy; and third, in automation with the use of the computer, and the fourth revolution known as Industry 4.0, according to the referenced researchers (Goecks et al, 2020;González & Calderón, 2018;González-Hernández & Granillo-Macías, 2020;Török, 2020;Zeidan & Bishno, 2020;Tihinen et al, 2021), based on digitalization and connectivity, generating important changes in the manufacturing industry, in consumer behavior, and business, leading them towards smart systems that efficiently use the potential of new technologies. digital technologies (Salah et al, 2020;Baena et al, 2017 studies the combination of physical and technological supports that offers the possibility of developing truly digital companies.…”
Section: Industrial Engineermentioning
confidence: 99%
“…(Motyl & Filippi, 2021); Digital skills comprise all skills related to the digital world, from basic digital literacy skills to specific digital skills for industrial professionals, suggesting a conceptual framework for digital skills that describes the coexistence of four dimensions: (1) technological, (2) cognitive, (3) ethical and (4) the integration of these three. González-Hernández & Granillo-Macías, (2020) cites the World Economic Forum (2018), which mentions that the ten generic skills or competencies necessary to prosper in Industry 4.0 are: complex problem solving, critical thinking, creativity, people management, coordination with others, emotional intelligence, judgment and decision making, service orientation, negotiation, and cognitive flexibility, and to specific skills, mentions that these should be focused on emerging technologies such as artificial intelligence and robotics, internet of things, virtual and augmented reality, additive manufacturing, blockchain, and distributed ledger technology, advanced materials, and nanomaterials, energy capture-storage and transmission, new computer technologies, biotechnologies, geoengineering, neuro-technology, and space technologies.…”
Section: Industrial Engineermentioning
confidence: 99%
See 1 more Smart Citation